2011
DOI: 10.1111/j.1552-6569.2011.00585.x
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Normal Cerebral Perfusion Patterns and White Matter Lesion Distribution in 1,249 Patients with Multiple Sclerosis

Abstract: Chronic plaques were more prevalent in WM regions with lower relative perfusion. Lesions in more highly perfused regions were more commonly observed in early RR MS and therefore, may be more likely to successfully remyelinate and resolve.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
53
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(61 citation statements)
references
References 34 publications
5
53
1
1
Order By: Relevance
“…However, it is worth pointing out that based on the lesion probability maps shown in this manuscript (Fig. 6) and published literature [Holland et al, 2012] on large cohorts, the juxtacortical lesion load is significantly lower than the deep WM lesion load.…”
Section: Table V Multivariate Regression On Cortical Thickness With mentioning
confidence: 52%
“…However, it is worth pointing out that based on the lesion probability maps shown in this manuscript (Fig. 6) and published literature [Holland et al, 2012] on large cohorts, the juxtacortical lesion load is significantly lower than the deep WM lesion load.…”
Section: Table V Multivariate Regression On Cortical Thickness With mentioning
confidence: 52%
“…6 The retinal hypoperfusion is in alignment with the observation of cerebral hypoperfusion in NAWGM in MS. 27,28 The cerebral hypoperfusion is considered a major step that induces a status defined as energy failure in MS. 29 According to a recent large scale clinical study on 1249 patients, MS lesions tend to occur in areas with lower perfusion. 30 …”
Section: Discussionmentioning
confidence: 99%
“…Many studies, using magnetic resonance imaging approaches, have found an impairment of about 50%, or more, of blood flow through NAWM of MS patients [2934]. Furthermore, the probability of developing MS lesions is greater in NAWM with the lowest perfusion rates [34]. One could argue that in MS, large areas of white matter may not function normally, thereby accounting for the reduced blood flow.…”
Section: Evidence For Hypoxia In Early Ms Lesionsmentioning
confidence: 99%